Quantifying nonlinear fracture parameters in bituminous SCB specimens: A compliance-based approach - Ince, Ragip; Yalcin, Erkut; Yilmaz, Mehmet (Elsevier, 2024)
Bituminous mixtures containing various defects, such as cracks and voids, exhibit ductile behavior in hot environments and brittle behavior in cold environments. Such materials can only be simulated realistically with the criteria of nonlinear fracture mechanics. In this investigation, the semi-circular bending (SCB) specimens, which have commonly been used to measure linear elastic fracture toughness parameters and fracture energy of asphalt and rock materials up to now, are studied to estimate several nonlinear fracture parameters of bituminous composites such as nonlinear fracture toughness, effective crack extension, critical crack tip opening displacement and brittleness. For this, the compliance functions of SCB specimens based on crack mouth opening displacement and load line displacement are derived by the finite element method at first. Subsequently, eight series of SCB tests in the literature, which were experimented with at low and room temperature environments, are examined by using two different compliance methods in fracture mechanics of quasi-brittle materials. This study's findings reveal that the crack extension in the pre-peak regime for mixes with bituminous at both low and normal temperatures is not statistically negligible and the use of nonlinear fracture toughness is, therefore, a necessity.
Keywords: Bituminous materials; Compliance methods; Fracture mechanics; Fracture toughness; Semi -circular bending specimen